The production of hydrogen peroxide during early-stage protein aggregation: a common pathological mechanism in different neurodegenerative diseases?. (1st August 2005) - Tabner, B.J.; Turnbull, S.; Fullwood, N.J.; German, M.; Allsop, D.
Abstract : By means of an ESR spin-trapping method, we have shown that Aβ (amyloid β), α-synuclein and various toxic forms of the prion protein all appear to generate H2 O2 in vitro . A fundamental molecular mechanism underlying the pathogenesis of cell death in several different neurodegenerative diseases could be the direct production of H2 O2 during the early stages of protein aggregation.